Telenursing through SMS (short messaging service): it’s effect on knowledge and adherence - Paragas, Erickson (Universiti Kebangsaan Malaysia, 2011)
The DeFIT it! Program utilizes the use of a diet diary and heath teaching through the use of SMS texting. It was designed for the respondents to acquire knowledge on proper diet and physical activity. The program aims prevention of weightrelated diseases such as Hypertension, Type II Diabetes mellitus, and cardiovascular diseases among overweight college students. The sample consisted of 24 students with a body mass index (BMI) between 25.00-25.99 kg/m2. Respondents in the experimental group were subjected to telenursing by receiving 4 daily short messaging services (SMS) for 21 days regarding health education on proper diet and physical activity, and reminders to follow the DeFIT it! Program. Both the experimental and control group were administered with a pretest and a posttest knowledge evaluation questionnaire before and after the implementation of the study, underwent a weekly body mass index assessment, and were given a DeFIT it! Booklet and DeFIT it! Diary during the initial contact with the respondents. Interestingly, statistical analysis of the data showed that there is a significant increase in the knowledge of telenursing users. However, there is no significant difference on the physical activity and diet adherence scores of telenursing users when compared to nontelenursing users. Also, it was observed that there is a significant decrease in the BMI of the nontelenursing users group which may be attributed to their low diet adherence scores. Thus, telenursing with the use of SMS is effective in increasing the subjects’ knowledge regarding proper diet and physical activity.